PENGARUH ARUS KAS OPERASI, INVESTASI, DAN PENDANAAN TERHADAP NILAI PERUSAHAAN PADA SEKTOR KEUANGAN DI INDONESIA - Fajri Fajri; Juanda Juanda (Departemen Manajemen, 2021)
This study aims to determine the effect of operating cash flow, investment cash flow, and financing cash flow on firm value in financial sector companies listed on the Indonesia Stock Exchange (BEI). This study uses panel data with 51 financial companies listed on the Indonesia Stock Exchange (BEI) from the 2014-2018 period. The analysis method used is multiple regression analysis with a fixed effect model. Partially the results of the study indicate that operating cash flow has a positive and insignificant effect on firm value. Investment cash flow has a negative and significant effect on firm value. Meanwhile, funding cash flows have a negative and insignificant effect on firm value. However, simultaneously operating cash flow, investment cash flow, and financing cash flow have affected positive and significant on firm value.